Velocity and Temperature Distributions Between Parallel Porous Plates with the Hall Effect and Variable Properties Under Exponential Decaying Pressure Gradient - Hazem Ali ATTIA; Mostafa A.M. ABDEEN (Engineering Transactions)
The time varying hydromagnetic flow between two infinite parallel porous plates is studied with heat transfer considering the Hall effect and temperature dependent physical properties. An exponential decaying pressure gradient is imposed in the axial direction and an external uniform magnetic field as well as a uniform suction and injection are applied perpendicular to the horizontal plates. A numerical solution for the governing non-linear coupled set of equations of motion and the energy equation is adopted. The effects of the Hall current and the tem- perature dependent viscosity and thermal conductivity on both the velocity and temperature distributions are investigated.